2015
DOI: 10.1007/s00027-015-0444-1
|View full text |Cite
|
Sign up to set email alerts
|

Responses to a warming trend and “El Niño” events in a tropical lake in western Mexico

Abstract: Lakes are sensitive ecosystems to climatic change but in the tropics it is frequently difficult to evaluate as there are few long-term records. In this paper hydrochemistry and phytoplankton data during the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 32 publications
2
23
0
4
Order By: Relevance
“…These conditions make these water bodies ideal for ecological and paleoecological studies because their sediments likely retain a detailed record of climate and environmental changes, both natural and anthropogenic. Some of these water bodies have already been affected by climate change (Gomez-Tagle et al, 2002;Caballero et al, 2015), which is worrying, since under these scenarios, we still lack baseline information about the microfauna inhabiting them. Therefore, up-to-date limnological investigation of these water bodies and the species dwelling there are required.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions make these water bodies ideal for ecological and paleoecological studies because their sediments likely retain a detailed record of climate and environmental changes, both natural and anthropogenic. Some of these water bodies have already been affected by climate change (Gomez-Tagle et al, 2002;Caballero et al, 2015), which is worrying, since under these scenarios, we still lack baseline information about the microfauna inhabiting them. Therefore, up-to-date limnological investigation of these water bodies and the species dwelling there are required.…”
Section: Introductionmentioning
confidence: 99%
“…In the modern climatic system, during El Niño events the ITCZ is displaced southward in the eastern tropical Pacific, which reduces summer precipitation in most of Mexico (Magaña et al, 2003). In the Alberca de Tacámbaro region, ENSO events are related to warmer dryer summers but cooler wetter winters (Magaña et al 2003, Pavia et al 2009, Caballero et al 2016. Caballero et al (2016) showed that the modern warming trend associated with a strong ENSO oscillation from 2009 to 2011 had an important effect on the phytoplankton diversity of this lake, showing that this ecosystem is highly sensitive to climatic variability.…”
Section: Climatic Forcingsmentioning
confidence: 99%
“…Las muestras se conservaron en refrigeración hasta ser analizadas en el laboratorio. Para estos análisis se siguieron los métodos analíticos descritos en Caballero et al (2016).…”
Section: Materiales Y Métodosunclassified
“…Las concentraciones de fósforo soluble reactivo (FSR) y de nitrógeno inorgánico disuelto (NID, la suma de amoniaco, nitritos y nitratos) en muestras de agua de distintas profundidades se presentan en la Figura 4; en esta figura se identifican fácilmente las muestras cuyas concentraciones de FSR y NID caen por debajo de 0.1 µM y 7 µM respectivamente, radiocarbono en un laboratorio comercial (Beta-324552: 126.1 ± 0.5 pMC). Esta datación se calibró con el programa CALIBBomb (Hua, Barbetti & Rakowski, 2013;Reimer et al, 2013) y se usó para generar un modelo de edad por interpolación polinomial entre el horizonte fechado y la cima de la secuencia (2006) (Caballero et al, 2016), lo que permite establecer que la sección de la secuencia estudiada data entre 1988 y 2006. Además, se colectaron muestras de sedimento superficial para análisis de diatomeas mediante una draga Ekman en agosto (verano) y octubre (otoño) de 2009, febrero (invierno) de 2010, junio (verano) de 2011, enero, abril, julio y noviembre (invierno, primavera, verano y otoño) de 2015.…”
Section: Materiales Y Métodosunclassified